Front seat development for autonomous driving: A case of innovative product development - Altun, Koray; Berber, Reyhan Özcan; Kurt, Recep; Bektaş, Enes; Turan, Sertan; Korkmaz, Varol (Gazi Üniversitesi, 2022)
Automotive trends and the strategies of automotive OEMs (Original Equipment Manufacturers) indicate that advanced and fully autonomous vehicles will appear in the market soon. In parallel with these progresses, customers’ needs and expectations for automotive parts will evolve accordingly. Particularly, since the seat is in physical contact with the user, it requires major improvements by employing novel functions to meet these evolved needs and expectations. This study addresses these novel front seat functions and provides a real case of development of an innovative front seat for autonomous driving. In this study, initially, new design ideas were generated regarding the front seats to meet changing customer needs. Generated ideas were evaluated through the QFD methodology. And, in line with these selected ideas, the style design, CAD design, and finite element analysis and testing activities were carried out. As a result of this study, an innovative front seat for autonomous driving has been developed, by taking the evolved customer expectations into account, and by verifying the design through finite element analysis and tests. Consequently, evolving customer needs for front seat by autonomous driving are assessed and a real innovative product development case is presented in this study. Future work can address other relevant interior parts of the automotive as to be appropriate for autonomous driving.

Otomotiv trendleri ve Orijinal Ürün Üreticileri (OEM-Original Equipment Manufacturer) stratejileri, ileri ve tam otonom araçların hızla piyasaya gireceğini göstermektedir. Bu gelişmelere paralel olarak, otomotiv parçaları için de müşterilerin ihtiyaç ve beklentileri değişecektir. Özellikle, koltukların kullanıcı ile fiziksel temas halinde olmasından dolayı, değişen müşteri ihtiyaçları ve beklentilerini karşılayabilmek için, yeni fonksiyonlar eklenilerek önemli derecede iyileştirilmesi gerekmektedir. Bu çalışma ile otonom sürüşe uygun yenilikçi otomotiv ön koltuğu geliştirilmiştir. Bu çalışma, yeni ön koltuk fonksiyonlarını ele almakta ve otonom sürüşe uygun yenilikçi ön koltuk geliştirme vakası sunmaktadır. Bu çalışmada, ilk olarak, ön koltuklar üzerinde değişen müşteri ihtiyaçlarını karşılayabilecek yeni tasarım fikirleri ortaya koyulmuş, Kalite Fonksiyon Göçerimi (QFD-Quality Function Deployment) metodolojisi ile değerlendirilmiş, belirlenen fikirler doğrultusunda stil tasarım, bilgisayar destekli tasarım, sonlu elemanlar analizi ve test faaliyetleri gerçekleştirilmiştir. Çalışma sonucunda, müşteri beklentilerini karşılayan, tasarımı sonlu elemanlar analizi ve testler ile doğrulanmış, otonom sürüş için yenilikçi bir ön koltuk geliştirilmiştir. Sonuç olarak, otonom sürüş ile birlikte değişen müşteri ihtiyaçları değerlendirilmiş ve gerçek bir yenilikçi ürün geliştirme vakası sunulmuştur. Gelecek çalışmalar, otonom sürüşe uygun olacak şekilde otomotivin diğer iç aksamlarını konu edinebilir.
Otonom sürüş için ön koltuk geliştirme: Yenilikçi ürün geliştirme vakası
3171072
Keywords: Engineering; Mühendislik